(The carved caves of the Great Mosque of Khurmal – Selected Examples – (An artistic, analytical, field research) - Hussein, Asst.L.Akram Shirwan Hussein; Mustafa, L. Mahdi jalal Mustafa; Majid, Rizgar Jawad Majid (Sulaimani Journal for Humanities, 2025)
Khurmal is one of the most important historical cities which is rich in many archaeological sites of the past periods of humanity, including mosques and minarets, cemeteries, castles, caves, Shura, Hill, etc. Therefore, it has always been of great importance to archaeologists and historians. It has been prominent is the historical books, documents and travelogues of the travelers who came to Kurdish territory. One of the most important monuments of the city is the carved gravestones of the Great Mosque. They are located in a square room in the western part of the mosque, which was destroyed due to past political unrest in the region and the influence of the climate and lack of public awareness to protect them from piece by piece destruction and many of the pieces are missing. Based on the historical records on the gravestones, we can see that the oldest of them dates back to the year (1239K/1824AD), they are decorated with botanical and geometric patterns along with writing patterns. The owners of the graves are the graves of Musa Beg, the governor at that time of Gulanbar and his family. The aim of the research is to reveal the history and importance of the place, the type of gravestones, patterns, lines and characteristics of the patterns on the gravestones, the artistic aspects of painting in the region, the names of those whose names are recorded, of course, this is important because these characters are buried here. They have had a significant role in the city
Keywords: Khurmal; Great Mosque; Map and Writing; Grave Cave